Effects of temperature on the formation of nitride surface layer via thermochemical gaseous nitriding process - Paijan, Lailatul Harina; Mamat, Mohd Fauzi; Abu Bakar, Mohd Hadzley; Maleque, Abd (Universiti Putra Malaysia, 2022)
Thermochemical gaseous nitriding is a surface modification process used for specific applications especially wear resistance components. The work aims to develop a formation of a modified surface layer on duplex stainless steel (DSS) using a gaseous thermochemical nitriding process using a tube furnace. This study investigated the effects of the nitriding temperature on the hardness and microstructure of the modified surface layers obtained on duplex stainless steel. The thickness of the hard surface layer, microstructure, phase composition, top surface and hardness profile were evaluated. The results obtained demonstrated that different temperatures influence the hardness and structural characterization of the nitrided samples. The expanded austenite in nitrided layer DSS improved the hardness performance 1 to 3 times higher than the untreated DSS that has strong correspondence to the formation of microstructural features, intermetallic compound and hard layer thickness. It was found that the nitrided layer at a temperature of 550 °C produced the highest hardness at the top surface with 603.4 Hv. However, the formation of chromium nitride contributes to the reduction of the corrosion resistance of duplex stainless steel. Therefore, the nitriding temperature at 450 °C experienced a hardness increment with 428.8 Hv and the thickest hard surface layer without the formation of chromium nitride.